Multimodal closed-loop strategies for gait recovery after spinal cord injury and stroke via the integration of robotics and neuromodulation - Valeria de Seta; Valeria de Seta; Simone Romeni; Simone Romeni (Frontiers in Neuroscience)
Restoring the ability to walk is a priority for individuals with neurological disorders or neurotraumatic injuries, given its significant impact on independence and quality of life. Multimodal closed-loop strategies that integrate robotic assistance and neuromodulation present promising avenues for personalized and physiological gait recovery. These approaches capitalize on residual motor activity, fostering neuroplasticity and motor relearning. This narrative review emphasizes the importance of mobile brain/body imaging (MoBI) for guiding the development of closed-loop systems that integrate volitional brain signals with residual motor activity in stroke and spinal cord injury patients. We explore the potential of rehabilitative and assistive interventional strategies based on robotic devices, such as exoskeletons and powered orthoses, and neuromodulation techniques like functional electrical stimulation and spinal cord stimulation. We highlight the limitations of the single interventional strategies and the potential of the synergistic combination of MoBI, robotics, and neuromodulation for gait recovery. By leveraging residual motor functions and integrating multimodal data from the different domains involved in motor recovery (i.e., brain, muscle, and biomechanics), the complementarity of these interventional strategies has the potential to enable dynamic patient-specific interventions. We outline a perspective framework on how future directions can exploit such integration to promote physiological recovery of lower limb functions and personalized therapies that are both challenging and feasible. Advancing along this path holds the promise of enhancing rehabilitative strategies, ultimately promoting functional recovery and long-term independence for individuals with neuromotor disorders.